Dicarbonyl stress mimics diabetic neurovascular damage in the retina - Kolibabka, Matthias; Friedrichs, Patrick; Dietrich, Nadine; Fleming, Thomas; Schlotterer, Andrea; Hammes, Hans-Peter (Experimental and clinical endocrinology & diabetes, 2016)
The net effect of euglycemic treatment is grossly overestimated in diabetes mellitus and retinopathy, similar to what is observed in diabetic individuals, is found in the absence of chronic hyperglycemia. Explanations of this clinical paradox include the excess generation of reactive intermediates of metabolism. Excess formation or impaired detoxification of reactive intermediates can also result in multiple posttranslational modifications with a wide range of cellular dysfunctions. The multicellular neurovascular unit represents the response element of the retina which is crucial for the development of diabetic retinopathy. Current evidence suggests that increased reactive intermediates in the retina induce (micro-)glial activation, neurodegeneration and vasoregression similar to alterations found in the diabetic retina. Reactive metabolites can be lowered by metabolic signal blockade, by an activation of detoxification pathways and by quenching. The translation of these novel findings into treatment of patients with complications is important to reduce individual suffering and financial burden for societies. Quick Summary:Increased levels of reactive intermediates, independent of blood glucose levels, are linked to damage of the neurovascular unit of the diabetic retina.